Training Communication and Attractive Appearance as Pro visions for Facing the World of Work for Sunan Drajat Lamongan Islamic Boarding School Students - Suci Yongki Setyowati; Munir, Akhmad Sirojudin; Luthfi Hidayah (PT. ALHAFI BERKAH INDONESIA, 2024)
Communication skills and attractive appearance play an important role in shaping an individual's professional image in the world of work. These two things are related to a student's readiness to start a career through an internship or work program. A student faces several obstacles in entering the world of work. One of the obstacles experienced is a lack of awareness of the importance of appearance and attitude in a career. This training aims to explore and influence physical appearance and communication in building a professional image. The activity participants were Islamic boarding school students and students of the Sunan Drajat Lamongan Islamic Boarding School. The training method is in the form of direct action in a training class/workshop for two hours. This activity was attended by 80 students. The evaluation results showed that from the training and briefing activities, it was seen that 60% of the participants had improved their communication skills and had an attractive appearance. This can be seen from the results of the final evaluation in the form of practical tasks carried out by the participants. A total of 48 participants were fluent in communication practices and had an attractive appearance. Furthermore, 20 or 25% of people are less able to practice communication and look attractive, another 12 or 15% of people are unable to practice communication or look attractive.